TECNOLOGIAS SUSTENTÁVEIS EM EDIFÍCIOS INSTITUCIONAIS - Tiburcio, Tulio M; Cal, Mariane; Andery, Paulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The construction industry is one of the sectors with great impact on the environment and it is the focus of this study. The literature indicates that sustainable development is a concept discussed in the academia, highlighting that public building must be designed in a sustainable way. This study seeks to investigate the insertion of sustainable technologies in institutional buildings in universities. This paper consists of an analysis of a pilot study in a specific building at Federal University of Viçosa, where the methodology was tested in order to be applied in a more comprehensive study in institutional buildings at Federal University of Minas Gerais. Results demonstrate a minimal insertion of sustainable technologies in the analysed building, which shows low concern with questions related to sustainability in the institutional buildings of the university. The methodology shown to be appropriate to map and investigate the research question.